A unified description of MCl3 systems with a polarizable ion simulation model - Hutchinson, F; Wilson, M; Madden, P (2001)
Computer simulations of a range of ionic systems of stoichiometry MX3 using a polarizable, formal charge ionic interaction model are described. The objective of the present work is to describe the optimization of the interaction potentials in the light of new structural information which has become available from neutron scattering studies of the liquid. As well as substantially improving the agreement with experiment for LaCl3, TbCl3, YCl3 and AlCl3, simulation results are presented for the first time for ScCl3, which is shown to exhibit a fascinating cross-linked network structure. The optimization of potentials for the crystal structures is also considered. It is shown that the Cl- ion must be considered as of smaller size in the crystal than in the liquid in order to successfully reproduce the properties of both phases.